Cleaning method of chicken feathers to obtain odorless fibers - Nazim Paşayev; Zübeyde Arabacilar; Mehmet Çadir (Journal of Natural Fibers, 2022)
In many cases, the processing of chicken feathers requires washing and disinfection. The unpleasant odor that remains on washed feathers after cleaning is a problem when using feathers or fibers derived from them. The odor of feathers is especially pronounced in high-temperature conditions. The aim of this study is to develop a method for cleaning chicken feathers, which makes it possible to obtain chicken feather fibers without unpleasant odor at a low cost. For this, the chicken feathers were washed according to different programs. Washed and unwashed feather were analyzed using GC-MS method to identify substances that can cause offensive odors at normal temperatures and under higher temperature conditions. The results of different cleaning methods were compared. It was found that the most effective cleaning method in terms of removing volatiles that can cause bad odor from feathers was a main wash with a nonionic detergent after a short prewash with sodium hypochlorite and a finishing treatment with sodium hydroxide solution. It was observed that the surface, internal structure, and mechanical properties of the feathers did not deteriorate as a result of this washing method.